Gold Nanoparticles Encapsulated Resveratrol as an Anti-Aging Agent to Delay Cataract Development - Qifang Chen; Peilin Gu; Xuemei Liu; Shaohua Hu; Hong Zheng; Ting Liu; Chongyi Li (MDPI AG, 2022)
Nanoparticle-based drug delivery systems, which can overcome the challenges associated with poor aqueous solubility and other harmful side effects of drugs, display potent applications in cataract treatment. Herein, we designed a nanosystem of gold nanoparticles containing resveratrol (RGNPs) as an anti-aging agent to delay cataracts. The spherical RGNPs had a superior ability to inhibit hydrogen peroxide-mediated oxidative stress damage, including reactive oxygen species (ROS) production, malondialdehyde (MDA) generation, and glutathione (GSH) consumption in the lens epithelial cells. Additionally, the present data showed that RGNPs could delay cellular senescence induced by oxidative stress by decreasing the protein levels of p16 and p21, reducing the ratio of BAX/BCL-2 and the senescence-associated secretory phenotype (SASP) in vitro. Moreover, the RGNPs could also clearly relieve sodium selenite-induced lens opacity in a rat cataract model. Our data indicated that cell senescence was reduced and cataracts were delayed upon treatment with RGNPs through activating the Sirt1/Nrf2 signaling pathway. Our findings suggested that RGNPs could serve as an anti-aging ingredient, highlighting their potential to delay cataract development.